Sex differences in pericardial adipose tissue assessed by PET/CT and association with cardiometabolic risk - Gill, Corey M. (Acta Radiol, 2018)
BACKGROUND: Recent studies suggest that pericardial adipose tissue (PAT) is associated with whole body adiposity and insulin resistance. Moreover, the incidence of cardiovascular disease (CVD) differs between men and women. Although CVD is more prevalent in men, women suffering from CVD have a higher mortality compared to men. Differences in PAT may account for some of the observed sex differences in manifestations of CVD. PURPOSE: To assess pericardial adipose tissue (PAT) as a biomarker for cardiometabolic risk and to assess potential sex differences. MATERIAL AND METHODS: We studied 303 subjects (151 women, 152 men, 57±17 yrs) across the weight spectrum. PAT and abdominal adipose tissue were quantified using clinical CTs obtained as part of a PET/CT. Cardiometabolic risk factors were assessed from medical records. Linear regression and ROC curve analyses were performed to evaluate associations between PAT and cardiometabolic risk. RESULTS: PAT was higher in overweight and obese compared to lean subjects and higher in men compared to women. PAT was positively associated with BMI, abdominal fat (p<0.0001), fasting glucose and serum lipids (p<0.05) with stronger associations in women than in men. PAT was accurate in detecting the prevalence of the metabolic syndrome with 74% sensitivity and 76% specificity (AUC=0.80). CONCLUSION: PAT is associated with measures of cardiometabolic risk and these associations are stronger in women compared to men. PAT could serve as a biomarker for opportunistic screening for cardiometabolic risk in patients undergoing chest CT.